Analisis Prediksi Financial Distress Menggunakan Pendekatan Model Altman dan Grover : (Studi pada Bank Muamalat Indonesia ) - Bakri Bakri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This study discusses the Altman and Grover models that lead to financial distress. The purpose of this study is to determine the extent of the two approaches between Grover and Altman in estimating the possibility of financial distress. The research study was conducted at Bank Muamalat by taking financial reports from 2015 to 2018. The research method used was descriptive quantitative using secondary data from the financial statements of PT. Bank Muamalat per quarter. The results of the study illustrate that with the Z-Score approach, Bank Muamalat can be predicted to experience financial distress in 2015, 2017 and 2018, this can happen, considering that the company's net profit has dropped significantly due to pressure on the company's main income account so that injections are needed. fresh funds from investors to continue their business. Another cause is the error of Bank Muamalat in carrying out a business strategy because it does not focus on corporate funding so that financing is problematic. As for using the G-Score approach which takes an indicator of the company's ability to generate working capital, so that it can pay its obligations, shows a condition where Bank Muamalat has no potential for bankruptcy and is still categorized as healthy.